MODEL PENGEMBANGAN WIRAUSAHAWAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM)YANG SUKSES - Tedy Ardiansyah (Sosio e-Kons, 2016)
Small Medium Enterprises (SME) activity has the most important role to progress the economy because this sector has been tested which has durability toward the economic crisis. SME provides greater employment opportunities, it can improve the welfare of society. But in reality, it is not easy to imagine. SME has also many problems, where a small business often face the test of nature with various difficulties, such as capital obstacle, human resources, government policy always changes, business location, competition, technology development and others. It is mentioned above as tweedledum and tweedledee. It is the same situation as entrepreneurs. Being a good entrepreneur can not easy to be realized, a lot of things need to be learned so it can open minded, it’s not enough only has well experiences but also has skills. Working hard without perseverance will be void and includes resistance toward the temptation that disturb in business activities. All of the above problems should have tricks so that the goal of entrepreneurship becomes successful. Keywords: SME, Change, Regeneration, Threat, Entrepreneurship, Capital, Temptation, Cluster and Perseverance.